Asymptomatic Intestinal Malrotation Progressing to Midgut Volvulus in a Decompensated Alcoholic Cirrhotic Adult: A Rare Scenario Requiring Special Considerations - Vatche Melkonian; Pablo Quadri; Chintalapati R. Varma; Mustafa Nazzal; Henry B. Randall; Minh-Tri J. P. Nguyen (Case Reports in Surgery)
Intestinal malrotation usually presents in the pediatric population with midgut volvulus requiring emergency Ladd’s procedure. Rarely, it remains asymptomatic and is discovered incidentally only during adulthood when it seldom causes intestinal complications. The scenario of a cirrhotic adult being diagnosed with asymptomatic intestinal malrotation with subsequent intestinal complications is thus extremely rare and to our knowledge has not been previously reported. We describe a 56-year-old man with decompensated alcoholic cirrhosis (Child-Pugh class C, MELD score 22) who was initially observed after an incidental diagnosis of intestinal malrotation on computed tomography. Observation continued as his liver disease improved with alcohol cessation (Child-Pugh class A, MELD score 8). He later presented with a closed loop bowel obstruction secondary to midgut volvulus at the time of alcohol relapse and liver redecompensation (Child-Pugh class C, MELD score 22-29). He underwent emergency Ladd’s procedure during which his midjejunum was volvulized into an internal hernia space created by a thick Ladd’s band containing large varices. The postoperative course was complicated by ileus and loculated bacterial peritonitis. Based on our experience, we discuss special considerations with regard to the surgical technique and timing of Ladd’s procedure when encountering intestinal malrotation in a cirrhotic adult with portal hypertension.